A single amino acid substitution in isozyme GST mu in Triclabendazole resistant Fasciola hepatica (Sligo strain) can substantially influence the manifestation of anthelmintic resistance - Fernández, V. (2015)
The helminth parasite Fasciola hepatica causes fascioliasis in human and domestic ruminants. Economic losses due to this infection are estimated in U$S 2000-3000 million yearly. The most common method of control is the use of anthelmintic drugs. However, there is an increased concern about the growing appearance of F. hepatica resistance to Triclabendazole (TCBZ), an anthelmintic with activity over adult and young flukes.F. hepatica has eight Glutathione S-Transferase (GST) isozymes, which are enzymes involved in the detoxification of a wide range of substrates through chemical conjugation with glutathione. In the present work we identified and characterized the GST mu gene isolated from the TCBZ-susceptible and TCBZ-resistant F. hepatica strains. Total RNA was transcribed into cDNA by reverse transcription and a 657 bp amplicon corresponding to the GST mu gene was obtained. The comparative genetic analysis of the GST mu gene of the TCBZ susceptible strain (Cullompton) and TCBZ resistant strain (Sligo) showed three nucleotide changes and one amino acid change at position 143 in the GST mu isozyme of the TCBZ-resistant strain.These results have potential relevance as they contribute better understand the mechanisms that generate resistance to anthelmintics.